Understanding HPV and cervical screening. (2nd January 2022) - Butler, Sarah; Wilkinson, Yvonne
Abstract : Cervical cancer is preventable and curable. Sarah Butler and Yvonne Wilkinson explain how the cervical screening programme has changed from a cytology based test to HPV primary screening Screening for human papillomavirus is now the primary test for cervical screening in England, Wales and Scotland. Cervical screening for those individuals with a cervix routinely occurs every 3 years for those aged 25–49 (24½ in England) and every 5 years for those aged 50–64. Over 99.7% of cervical cancers are caused by human papillomavirus. Cervical cancer is preventable and curable; primary HPV screening can detect early changes in cervical cells allowing for effective monitoring and treatment.